Cost of the quanta SC+ hemodialysis system for self‐care in the United Kingdom. Issue 3 (9th January 2022) - Ferguson, Thomas W.; Harper, Gerard D.; Milad, John E.; Komenda, Paul V. J.
Abstract: Introduction: New personal hemodialysis systems, such as the quanta SC+, are being developed; these systems are smaller and simpler to use while providing the clearances of conventional systems. Increasing the uptake of lower‐intensity assistance and full self‐care dialysis may provide economic benefits to the public health payer. In the United Kingdom, most hemodialysis patients currently receive facility‐based dialysis costing more than £36, 350 per year including patient transport. As such, we aimed to describe the annual costs of using the SC+ hemodialysis system in the United Kingdom for 3×‐weekly and 3.5×‐weekly dialysis regimens, for self‐care hemodialysis provided both in‐center and at home. Methods: We applied a cost minimization approach. Costs for human resources, equipment, and consumables were sourced from the dialysis machine developer (Quanta Dialysis Technologies) based upon discussions with dialysis providers. Facility overhead expenses and transport costs were taken from a review of the literature. Findings: Annual costs associated with the use of the SC+ hemodialysis system were estimated to be £26, 642 for hemodialysis provided 3× weekly as home self‐care; £30, 235 for hemodialysis provided 3× weekly as self‐care in‐center; £29, 866 for hemodialysis provided 3.5× weekly as home self‐care; and £36, 185 for hemodialysis provided 3.5× weekly as self‐care in‐center. Discussion: We found that the SC+ hemodialysis system offers improved cost‐effectiveness for both 3×‐weekly and 3.5×‐weekly self‐care dialysis performed at home or as self‐care in‐center versus fully assisted dialysis provided 3× weekly with conventional machines in facilities.